2012
DOI: 10.1128/jvi.06346-11
|View full text |Cite
|
Sign up to set email alerts
|

Filoviruses Require Endosomal Cysteine Proteases for Entry but Exhibit Distinct Protease Preferences

Abstract: , we found that virus-specific differences in the requirement for cathepsin B are correlated with sequence polymorphisms at residues 47 in GP1 and 584 in GP2. We applied these findings to the analysis of additional ebolavirus isolates and correctly predicted that the newly identified ebolavirus species Bundibugyo, containing D47 and I584, is cathepsin B dependent and that ebolavirus Zaire-1995, the single known isolate of ebolavirus Zaire that lacks D47, is not. We also obtained evidence for virusspecific diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
152
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(165 citation statements)
references
References 45 publications
9
152
2
Order By: Relevance
“…Of note, α5β1 integrin is required for cathepsins B and L to be catalytically active for GP priming [49], supporting an earlier study showing the importance of integrins for filovirus entry [50]. However, since each filovirus species has a different dependency on cathepsin-processing [51,52] and mouseadapted ebolavirus retains full pathogenicity in mice deficient in either cathepsin B or L [53], other important host proteases are likely involved in proteolytic processing of GPs.…”
Section: Entrysupporting
confidence: 60%
“…Of note, α5β1 integrin is required for cathepsins B and L to be catalytically active for GP priming [49], supporting an earlier study showing the importance of integrins for filovirus entry [50]. However, since each filovirus species has a different dependency on cathepsin-processing [51,52] and mouseadapted ebolavirus retains full pathogenicity in mice deficient in either cathepsin B or L [53], other important host proteases are likely involved in proteolytic processing of GPs.…”
Section: Entrysupporting
confidence: 60%
“…FY-dmk at the lowest concentration tested in this study (0.625 M) did not reduce infectivities of VSV⌬G*-Lloviu, VSV⌬G*-Zaire, or VSV⌬G*-Angola, suggesting that cathepsin L is not essential for LLOV infection, similar to the other filoviruses (40,41). It was also shown that cathepsin B and cathepsin L activities are not required for EBOV replication in a mouse model (41).…”
Section: Discussionmentioning
confidence: 55%
“…However, the requirement of cathepsin L might be controversial, since a high concentration (Ͼ1 M) of FY-dmk was suggested to inhibit not only cathepsin L but also cathepsin B and likely other endosomal cysteine proteases (40). FY-dmk at the lowest concentration tested in this study (0.625 M) did not reduce infectivities of VSV⌬G*-Lloviu, VSV⌬G*-Zaire, or VSV⌬G*-Angola, suggesting that cathepsin L is not essential for LLOV infection, similar to the other filoviruses (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the fact that the other 19 compounds affected only MARV indicates that specific differences in cell entry may be exploited in studying infection mechanisms unique for each virus. Indeed, this is supported by work showing that each virus has different dependencies on cellular proteases for activation of the GP for membrane fusion (22,23) and is potentially the reason that none of the broadly active compounds were found to be cathepsin protease inhibitors.…”
Section: Discussionmentioning
confidence: 94%
“…Filoviral GP binds receptors, and the virus is internalized through macropinocytosis (18,19) and trafficked through endosomes, which is dependent on the calcium channel TPC2 (14,20). During trafficking the virus is exposed to an increasingly acidic environment, in which proteases are activated and cleave the GP (21)(22)(23)(24), allowing interaction with NPC1, a key protein found in endosomes (25,26).…”
mentioning
confidence: 99%